Impact of Users' Attitudes Toward Anonymous Internet Interventions for Cannabis vs. Alcohol Use: A Secondary Analysis of Data From Two Clinical Trials - Romero, Danilo; Johansson, Magnus; Hermansson, Ulric; Lindner, Philip (Frontiers in Psychiatry, 2021)
Background: Numerous trials have demonstrated the efficacy of internet interventions targeting alcohol or cannabis use, yet a substantial proportion of users do not benefit from the format, warranting further research to identify moderators of treatment effects. Users’ initial attitudes towards treatment is a potential moderator, yet no previous study has investigated users’ attitudes in the context of internet interventions for addictive disorders. Method: In this secondary analysis on two internet-based trials targeting harmful alcohol use (n=1169) and regular cannabis use (n=303), respectively, we compared user groups’ attitudes at the item level; explored within-group heterogeneity by submitting attitude scores to a k-means cluster analysis; and investigated whether latent subgroups in each user group moderated the treatment effects. Outcome models were run using generalized linear models with 10 000 bias-corrected bootstraps accounting for subject-level clustering. Results: While substance groups and latent subgroups converged in enjoying the anonymity provided by the format, their interest towards treatment differed. Outcome analyses revealed a significant and negative time by subgroup effect on grams of cannabis consumed and screening test score (CAST), favoring the subgroup with positive treatment attitudes. There were not any significant effects of subgroup on alcohol consumption. Despite initial treatment reluctance, participants in the neutral subgroup decreased their cannabis use (gram) significantly when receiving the intervention versus control. Conclusions: This first, exploratory study revealed key differences between substance groups’ attitudes, but more importantly that within-group heterogeneity appear to affect cannabis outcomes. Assessing attitudes could be key in patient-treatment matching, yet more research is needed.